MobiScan: An enhanced invisible screen‐camera communication system for IoT applications. Issue 4 (15th December 2020) - Zhang, Xiao; Liu, Jiqiang; Ba, Zhongjie; Tao, Yaodong; Cheng, Xiaochun
Abstract: In recent years, dynamic and invisible screen‐camera short‐range communication for IoT devices have become a popular research field due to its superior user experience and no‐extra hardware required. However, most existing screen‐camera communication systems suffer from poor data security, high computational overhead, and limited capture angle, which make them infeasible in practice. In this work, we propose MobiScan, a dynamic and invisible screen‐to‐camera communication system that is able to ensure data security, real‐time communication, and flexible capture angle. MobiScan is composed of two parts: a novel fast frame correction scheme and a multilevel data pattern scheme to address the above problems. The fast frame correction scheme proposes a novel frame correct approach that utilizes the sensor data on the smartphone to correct the captured frame by reproducing the relationship between positions of the screen and the smartphone. Through this method, the scheme can save frame correction time without calculating frame content to identify the degree of deformation. The multilevel data pattern scheme protects the data privacy by sending the classified information to targeted users, which can reduce the time overhead and extend the application scenario by redesigning the data structure. The experimental results show that for flexible capture angle problem, the maximum capture angle is 180° in the rotate view and 60° in the side view, bottom view, and overlook view. For real‐time communication problem, the time overhead is reduced by 90% in the procedure of the frame correction. In the data decoding process, the time overhead is reduced by 10%. MobiScan enables a flexible capture angle on the PC platform for secure and real‐time communication. Abstract : We propose MobiScan, a dynamic and invisible screen‐to‐camera communication system that is able to ensure data security, real‐time communication, and flexible capture angle. MobiScan is composed of two parts: a novel fast frame correction scheme and a multilevel data pattern scheme to achieve above goals. The experimental results show that the maximum capture angle is 180° in the rotate view and 60° in the side view, bottom view, and overlook view. The time overhead is reduced by 90% in the procedure of the frame correction